Effect of Pole Number on Generator End Winding Electromagnetic Force and Mechanical Response before and after RISC. (23rd December 2021) - Jiang, Hong-Chun; He, Yu-Ling; Tang, Gui-Ji
Abstract : This paper comparatively studies on the end winding electromagnetic force and mechanical response for generators with different numbers of poles. The analytical expression of the end winding electromagnetic force is derived under the rotor winding interturn short circuit (RISC) considering the pole number. Meanwhile, the three-dimensional transient finite element simulation is carried on two generators with one-pair poles and three-pair poles. Then, the frequency composition and amplitude variation characteristics of the radial, axial, and tangential electromagnetic forces are analyzed. Further, the maximum stress and deformation on the end winding are calculated and the similarity and difference of the coil failure law are obtained for two kinds of generators. It is found that RISC will bring odd harmonics to electromagnetic force for one-pair pole generators but it will bring odd and fraction harmonics for multipair pole generators. Moreover, the max mechanical response under RISC will decrease for one-pair pole generators but it will increase for multipair pole generators.